NARRATIVAS TRANSMEDIA EN LA ERA DE LA SOCIEDAD MÓVIL. CARLOS, REY EMPERADOR - Ddo. JOSÉ L. CARREÑO VILLADA, (Fonseca, Journal of Communication, 2023)
Transmedia narratives are an integral part of mobile communication and are becoming one of the most recurrent when presenting a new audiovisual format forms. Carlos, King Emperor series makes use of transmedia storytelling to reach the user and interact with it through the different elements of your macro narrative universe, elements such as video game or profiles on social networks.